FACIAL NERVE PARESIS FOLLOWING RECONSTRUCTION OF NEGLECTED MANDIBULAR CONDYLE FRACTURE: SURGICAL CONSIDERATIONS AND ADJUNCTIVE NEUROTROPHIC THERAPY - Putu Kania Iswari Niramayah; I Nyoman Putu Riasa; Bertha Kawilarang; Felicia Adelina Shannen (Universitas Airlangga, 2026)
Highlights: Delayed mandibular condylar fractures pose reconstructive challenges due to bone remodeling, with management options including condylar reconstruction or orthognathic surgery. A combined preauricular–retromandibular approach provides adequate exposure but carries a risk of facial nerve paresis, with outcomes inconsistently reported in the literature. Adjunctive oral mecobalamin appears safe and may support recovery in postoperative facial nerve paresis. Abstract: Introduction: Although mandibular condyle fractures are common, their treatment remains debatable, especially in neglected or delayed cases. Delayed cases often present with malunion and functional limitation and are associated with increased surgical difficulty. Facial nerve injury is a well-known complication of condylar reconstruction, but it remains underreported in delayed cases. Evidence guiding the management of delayed or revision cases is limited, and standardized treatment protocols are lacking. Case Illustration: A 47-year-old man with neglected mandibular fractures and left TMJ dislocation underwent initial ORIF and fixation. Persistent malocclusion and pain led to definitive osteotomy and ORIF of the left condyle via a combined preauricular and retromandibular approach. We present a case of neglected mandibular condylar fracture managed with osteotomy, reduction, and internal fixation using a combined preauricular–retromandibular approach. A scoping review of PubMed and Scopus was performed to evaluate surgical strategies for delayed or malunited condylar fractures. Of 238 records identified, six studies met inclusion criteria. Discussion: Included studies showed heterogeneous definitions and surgical approaches (condylar reconstruction and orthognathic surgery), both yielding satisfactory occlusion and function. Facial nerve outcomes were rarely reported. In this case, frontal branch paresis occurred postoperatively and nearly fully recovered within six months with conservative therapy and mecobalamin. Conclusion: Delayed condylar fractures require individualized, often complex surgical correction. Facial nerve morbidity remains insufficiently characterized. Oral mecobalamin appears safe and may support nerve recovery, although its clinical benefit requires validation. Development of standardized protocols for delayed or revision cases is warranted.